2011
DOI: 10.1016/j.jmmm.2011.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into ferrofluid magnetoviscous effects under an oscillating shear flow

Abstract: a b s t r a c tThe use of ferrofluid seals in mechanical systems can lead to viscous damping that affects their dynamic behavior. This paper describes an investigation into local viscous properties in the case of an axial harmonic force. The influence of magnetic field level, shear stress amplitude and frequency are studied. Even for ferrofluid particles in a highly saturated magnetic field, it is shown that viscosity increases with magnetic intensity, decreases with the frequency of harmonic excitation and is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…These chains increase the resistance to the flow, thereby increasing viscosity. This is consistent with previous studies [8,[18][19][20][21].…”
Section: Transport Properties Viscositysupporting
confidence: 94%
See 1 more Smart Citation
“…These chains increase the resistance to the flow, thereby increasing viscosity. This is consistent with previous studies [8,[18][19][20][21].…”
Section: Transport Properties Viscositysupporting
confidence: 94%
“…Table A2 in the appendix compiles past experimental results for ferrofluid viscosity. Past experimental results have agreed that viscosity increases with an increasing solid volume concentration and magnetic flux strength, and viscosity decreases with increasing temperature [8,[18][19][20][21]. Li et al [18] and Wang et al [19] found that the rate of increase in viscosity is reduced with increasing solid volume concentration, magnetic flux strength and temperature.…”
Section: 2mentioning
confidence: 77%
“…It is also observed that the critical strain marking the onset of nonlinearity decreases with magnetic field up to 160 mT and slightly increases thereafter. The response of ferrofluid to an oscillatory shear studied by Pinho et al 29 reveals that the viscosity increases with magnetic field and monotonically decreases with oscillation frequency. A similar observation was recorded for the viscous damping force on an oscillating plate in contact with ferrofluid subjected to a constant magnetic field.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, ferrofluids with fairly monodisperse particles and excellent long-term stability can be tailored. The magneto-rheological properties of ferrofluids have been studied both theoretically and experimentally. , Though steady shear behavior of ferrofluids has been well characterized, only a few studies concentrate on their oscillatory behavior, , where the particles are considered to be noninteracting.…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, oscillatory shear experiments have received little application in the study of ferrofluids, even though chain formation, deformation, and breakage are also important processes that determine the magnetorheological properties of ferrofluids [47]. Recently, Pinho et al [48] reported a series of oscillatory shear measurements with commercial ferrofluids in applied magnetic fields. They only reported viscous damping of the force on an oscillating plate in contact with ferrofluid subjected to a constant magnetic field.…”
Section: Introductionmentioning
confidence: 99%